Confronting Colorblind Commodity Racism: Young Jean Lee’s The Shipment - Hwang, Seunghyun (American Studies in Scandinavia, 2021)
Surrounded by the hubbub of the 2008 presidential election, playwright Young Jean Lee considered a topic for the next project of her nonprofit experimental theater company and decided to write a black identity politics show that addressed the issues of commodity racism and perceived colorblindness. Her objective, in collaboration with five African American actors, was to expose both conscious and unconscious racial stereotyping deeply rooted in American culture and to lead the audience to connect the abstract element of racial stereotyping to the actual experiences of minority individuals. This article focuses on the development process of the 2008 project and connects it to the social, cultural and political influences that guided the process to demonstrate how the production fits into the historical landscape of dramatic literature and to illustrate the power of the performing arts as a catalyst to initiate public dialogue and to bring to the forefront the questioning of discriminative societal attitudes and practices.